Antroponimy w listach prywatnych Henryka Sienkiewicza na przykładzie nazw osobowych członków rodziny pisarza - Mariak, Leonarda (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2025)
The article contains a formal, functional and structural analysis of unofficial anthroponyms (names, nicknames) used by Sienkiewicz to refer to members of his family. The material, consisting of over 150 units, was collected by linear excerption from the entire preserved private correspondence of the writer, consisting of over 1,400 letters, which occupy approximately 3,000 pages of text in the Listy Sienkiewicza (Sienkiewicz’s letters) collection edited by Maria Bokszczanin. The correspondence was addressed to seven members of the writer’s closest family, i.e. three successive wives, two children, a sister-in-law and his younger sister. The repertoire of collected anthroponyms includes unofficial personal names, such as: Mańcia, Marylka, Maryluś, Marynia, Nadmarynia; Dzideczek, Dzidek, Dzidka, Dziduś, Dzidzio, Dzidziu, Dzidziuś and nicknames, e.g.: Frog, Kociątko, Kot, Kotek, Kurczątko, Przyjaciel, Sally, Salomon, Siostrzyczka, Sowietnik, Szarotka, Ziaba, Żaba, Żabeusz, Żabka, Żabu. Pani Żabińska. Particular attention was paid to word-forming phenomena, especially the formants by means of which Sienkiewicz transformed the official metrical form of a name into an unusual, original and emotionally charged proper name denoting a close person. The study also takes into account the relationship of name-forming acts with the writer’s extralinguistic family reality.